The economics of green building: the green rental premium in Johannesburg - Bruni, Jade (My University, 2017)
This research focuses on the green building rental premium that is associated with the Green Star SA rating tool within the commercial property sector (and particularly offices), in Johannesburg. Financial factors are integral in decision-making for investors and developers in the development and management of real estate. Simply put, increased financial benefits, decreased financial costs and low levels of risk are signals for the inception of real estate developments. The general sentiment from investors and developers is that, regarding green buildings, there is no incentive to justify moving away from a ‘business as usual’ approach and the development of conventional buildings. Limited research, both internationally and locally, has not assisted in rectifying these sentiments, which has hindered the growth of green building in the real estate market and the mitigation of the negative environmental effects that are associated with buildings and the built environment. Descriptive statistics and hedonic regression analyses were utilised in order to determine and calculate a rental rate premium associated with office buildings in Johannesburg which have a Green Star rating. A rental premium of 4,5% was determined by employing hedonic regression analyses from data that were collected for 30 Green Star rated buildings and 30 conventional buildings, which are multi-tenanted office buildings with Triple Net leases, in 7 geographical areas in Johannesburg. It was determined that the variables affecting rental price and the rental premium in Johannesburg are in line with international literature.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Architecture in Sustainable and Energy Efficient Cities. Johannesburg, 2017.
Keywords: Sustainable buildings--Johannesburg; Green movement--Johannesburg; Sustainable buildings--Design and construction--Costs; Sustainable architecture--Johannesburg; Office buildings--Design and construction--Environmental aspects